Understanding Poverty of the First Goal of SDGs: An Analysis of Contributing Factors - Yuan, Mikael Amy; Pratiwi, Pintari (PT Global Digital Sains Tekno, 2024)
The level of poverty in Sumatra is one of the poverty problems that need a solution in accordance with the first goal of the Sustainable Development Goals (SDGs). The reason for choosing the Poverty Level in Sumatra as the research object is because the problem of poverty has the potential to create social problems and low access to various kinds of resources and productive assets, as well as fulfilling basic human needs, both food and non-food. The problem of poverty has an impact on the quality of human resources. This research aims to analyze the influence of the Dependency Ratio, Government Expenditure, Population Growth and Job Opportunities on Poverty Levels in Sumatra. The variables used are Dependency Ratio, Government Expenditure, Population Growth and Job Opportunities. The data used in this research is secondary data taken over a period of 15 years. Secondary data was obtained from the Sumatra Central Statistics Agency (BPS). For data analysis, computer tools were used, including the SPSS (Statistics Program for Social Science) program version 13.00. The analysis used in this research is multiple linear regression, and the hypothesis tests used are the t-test and statistical F-test. The test results prove that the Dependency Ratio and Job Opportunities influence the poverty level in Sumatra. Meanwhile, the results of testing Government Expenditures and Population Growth do not affect the Poverty Level in Sumatra.